5
![5x2 - 3x + 9 = - 6 x2 - 5x + 1 5x2 - 3x + 9 = - 6 x2 - 5x + 1](https://tex.z-dn.net/?f=5x2+-+3x+%2B+9+%3D++-+6+x2+-+5x+%2B+1)
Soluções para a tarefa
Respondido por
0
Resposta:
1) 4x – 1 = 7 2) 3x – 9 = 12 3) 3x + 2 = 4x + 9 4) 5x – 2 + 12 = 6x + 4 5) 2x ... 6 26) x - 7 + 2 ( x – 4) = -3 (x + 2) – 8 27) 28) 29) 30) x 3 − 1 2 = − x 3.
Perguntas interessantes
Biologia,
7 meses atrás
Administração,
7 meses atrás
Saúde,
7 meses atrás
Inglês,
9 meses atrás
Administração,
9 meses atrás
Física,
1 ano atrás
Química,
1 ano atrás